SOCIODEMOGRAPHIC FACTORS AFFECTING PATIENT COMPLIANCE TO LONG-TERM THERAPIES - MIR, SHAKEEL AHMAD (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The aim is to study the effect of various sociodemographic factors on patient compliance in long-term therapies. Methods: This is a questionnaire-based study of 195 adult outdoor patients suffering from chronic illnesses and receiving long-term drug therapy. Various sociodemographic factors were noted in a validated questionnaire. Questions about drugs being taken were asked. The compliance was measured by General Medication Adherence Scale. Results: The study population consists of 51.3% of males and 48.7% of females. About 39.0% of participants were literate and 61.0% were illiterate. About 72.3% belonged to the rural area, 13.3% urban, and 14.4% to the main city. About 33.3% were self-employed or unemployed, 17.4% government employees, and 49.3% were private employees. About 20.0% belonged to high-income group, and 40.0% to middle- and 40.0% to low-income group. Statistically significant correlation was found between compliance and age, gender, area of residence, education, and marital status (p<0.05). Better compliance was observed in men, unmarried,middle-aged, literate, and urban populations. Conclusions: We conclude that some sociodemographic factors correlate with compliance to long-term therapies.